2017
DOI: 10.2147/prom.s140678
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire-based audit to assess overall experience and convenience among patients using vaginal progesterone tablets (Lutigest<sup>&reg;</sup>) for luteal phase support during IVF treatment

Abstract: PurposeThe aim of this audit was to assess the overall experience and patient convenience of vaginal progesterone tablets (Lutigest®, marketed as Endometrin® in the USA) used for luteal phase support (LPS) during in vitro fertilization (IVF) treatment.Patients and methodsThis questionnaire-based audit included responses from 100 patients undergoing IVF treatment at six IVF clinics in the UK from September 2015 to November 2016. Fourteen days after starting progesterone supplementation for LPS during their IVF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Assuming similar safety and efficacy profiles, it is important to be able to offer women treatment options that relate to convenience of use. Vaginal products are preferred by many women over injections, but are still not ideal as they involve several daily administrations that require finding a private clean room where the vaginal progesterone can be administered and the woman can lie flat for several minutes following insertion; furthermore, vaginal discharge/leakage, vaginal build-up, vaginal irritation, vaginal itching and perineal irritation are common (Heine et al, 2017). A questionnaire-based survey of 100 women in the USA reported that the majority found vaginal progesterone tablets to be more comfortable and more convenient compared with pessary administration (60.6% versus 30.3% and 57.6% versus 39.4%, respectively) (Heine et al, 2017).…”
Section: The Use Of Dydrogesterone In Assisted Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming similar safety and efficacy profiles, it is important to be able to offer women treatment options that relate to convenience of use. Vaginal products are preferred by many women over injections, but are still not ideal as they involve several daily administrations that require finding a private clean room where the vaginal progesterone can be administered and the woman can lie flat for several minutes following insertion; furthermore, vaginal discharge/leakage, vaginal build-up, vaginal irritation, vaginal itching and perineal irritation are common (Heine et al, 2017). A questionnaire-based survey of 100 women in the USA reported that the majority found vaginal progesterone tablets to be more comfortable and more convenient compared with pessary administration (60.6% versus 30.3% and 57.6% versus 39.4%, respectively) (Heine et al, 2017).…”
Section: The Use Of Dydrogesterone In Assisted Reproductionmentioning
confidence: 99%
“…Vaginal products are preferred by many women over injections, but are still not ideal as they involve several daily administrations that require finding a private clean room where the vaginal progesterone can be administered and the woman can lie flat for several minutes following insertion; furthermore, vaginal discharge/leakage, vaginal build-up, vaginal irritation, vaginal itching and perineal irritation are common (Heine et al, 2017). A questionnaire-based survey of 100 women in the USA reported that the majority found vaginal progesterone tablets to be more comfortable and more convenient compared with pessary administration (60.6% versus 30.3% and 57.6% versus 39.4%, respectively) (Heine et al, 2017). A prospective randomized study comparing MVP with oral dydrogesterone as luteal phase support after IVF reported that vaginal discharge or irritation were reported by 10.5% of patients given MVP and that significantly more patients were satisfied with the tolerability of dydrogesterone than with that of MVP (Chakravarty et al, 2005).…”
Section: The Use Of Dydrogesterone In Assisted Reproductionmentioning
confidence: 99%
“…17P SNEDDS-loaded vaginal tablets would be much easier to use and more affordable compared to both IM and SC injections. The vaginal route leads to a higher endometrial concentration compared to IM injection [37,38,39]. Moreover, due to the complexity of the technology used here, production in a compounding setting is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…During the luteal phase, the corpus luteum produces progesterone, which prepares the estrogen-primed endometrium for embryo implantation ( Heine et al ., 2017 ). Progesterone is known to be an essential hormone required for successful implantation and continuation of early pregnancy by inducing sequential events in the endometrium during the luteal phase, including maturation, secretory transformation of the glandular elements, edema formation, vascular proliferation and stroma decidualization ( Heine et al ., 2017 ; Ho et al ., 2008 ; Satir et al ., 2013 ; Beltsos et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the luteal phase, the corpus luteum produces progesterone, which prepares the estrogen-primed endometrium for embryo implantation ( Heine et al ., 2017 ). Progesterone is known to be an essential hormone required for successful implantation and continuation of early pregnancy by inducing sequential events in the endometrium during the luteal phase, including maturation, secretory transformation of the glandular elements, edema formation, vascular proliferation and stroma decidualization ( Heine et al ., 2017 ; Ho et al ., 2008 ; Satir et al ., 2013 ; Beltsos et al ., 2014 ). In assisted reproductive technology (ART) treatment, the down regulation of luteinizing hormone (LH) secretion by the use of gonadotropin-releasing hormone (GnRH) agonists or antagonists, can lead to luteal phase disruption as the amount of progesterone produced is not sufficient; this can lead to ineffective development of the endometrium, hence reduction in the implantation rate ( Heine et al ., 2017 ; Ho et al ., 2008 ; Satir et al ., 2013 ; Beltsos et al ., 2014 ; Bahceci & Ulug, 2008 ).…”
Section: Introductionmentioning
confidence: 99%